Hybridity In New Media: A Pre-Production Guideline - Arya Harditya (Indonesian Journal of Computing, Engineering, and Design (IJoCED), 2019)
‘New’ technologies have disrupted the creative process of arts and media production, but no common professional practice seems to have drastically changed. ‘New' is only a trick, a temporary euphoria indicating that creative arts and media are on its way to the utopian future. Currently, creative arts and media practitioners are influenced by the dynamically developing technologies and the big issue is that they accepted every innovational media technology unknowingly, everything is normal, but every changes lead to a new normal. The purpose of this paper is to discover the new creative production process that influenced by new technologies. In the process of discovery, this paper uses a Practice-based Research methodology by Estelle Barrett to acknowledge the capability of these media technologies by utilising creative practices. All findings in this research are discovered by experimenting on contemporary audio visual and interactive technologies. The result of this journal is a guideline for preparing new media production.